A 3D-Printed Zeolitic Imidazolate Framework-8 Monolith For Flue- and Biogas Separations by Adsorption: Influence of Flow Distribution and Process Parameters - Verougstraete, Brieuc; Schuddinck, Dieter; Lefevere, Jasper; Baron, Gino V.; Denayer, Joeri F. M. (Frontiers in Chemical Engineering, 2020)
Improving the efficiency of gas separation processes for CO2 capture is primordial. In the field of adsorptive separation processes, a shift to structured adsorbents, more especially monoliths, can be seen. These offer better efficiency, better mass transfer characteristics and a lower pressure drop compared to the conventional shape of adsorbents. This could lead to short adsorption/desorption cycles, which is crucial. In this study we analyzed a 3D-fiber deposited ZIF-8 monolith. The resulting interwoven structure of the monolith has the advantage to allow for radial diffusion in between the channels. Therefore, the gas flow distribution inside the monolith was investigated. This was done experimentally, but also in silico. Next, breakthrough experiments were performed to study the influence of flow rate and desorption time, since ZIF-8 can easily be regenerated. It was seen that flowing air through the monolith for 6 s was sufficient to regenerate the monolith. Regarding the hydrophobicity of ZIF-8, the presence of water vapor in the gas stream was investigated. Lastly, the selectivity of ZIF-8 for CO2 over CH4 was determined.